Bioconversion of sucrose to maltooligosaccharides by the synergistic action of amylosucrase and α-amylase. (November 2018) - Zhu, Xingtong; Tian, Yuqing; Xu, Wei; Guang, Cuie; Zhang, Wenli; Zhang, Tao; Mu, Wanmeng
Graphical abstract: Highlights: A novel α-amylase from Pseudomonas mendocina was partially characterized. A dual enzyme strategy was developed to produce MOS from sucrose. In the one-pot enzymatic reaction, a maximum MOS yield of 22.8% was achieved. In the two-step enzymatic reaction, the highest MOS production yield was 34.1%. Abstract: Maltooligosaccharides (MOS), oligosaccharides composed of 2 to 10 glucopyranose subunits linked by α-1, 4 bonds, are promising ingredients possessing low sweetness, low osmolality, high water-holding capacity, and crystallization-prevention ability. For improved the cost effectiveness, a novel process for MOS preparation was developed by utilizing sucrose as a raw material instead of starch. In this work, a novel α-amylase from Pseudomonas mendocina (PM-Amy) was characterized and applied to produce the MOS from α-1, 4-glucans obtained by the amylosucrase treatment of sucrose. PM-Amy showed a maximum activity at a pH of 6.0 and 55 °C. In the one-pot enzymatic reaction, a maximum MOS yield of 22.8% (w/w) was achieved, while the highest MOS yield (34.1%, w/w) was achieved from the two-step dual enzyme reaction.